2023
DOI: 10.1186/s12889-023-16927-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between psychological resilience and quality of life among the Chinese diabetes patients: the mediating role of stigma and the moderating role of empowerment

Yujin Mei,
Xue Yang,
Jiaofeng Gui
et al.

Abstract: Background Although some factors, such as stigma and empowerment, influence the complex relationship between psychological resilience and quality of life, few studies have explored similar psychological mechanisms among patients with diabetes. Therefore, this study explored the mediating role of stigma and the moderating role of empowerment in the psychological mechanisms by which psychological resilience affects quality of life. Methods From June … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Additionally, when dealing with the obstacles and challenges of their condition, it can assist people with chronic diseases in being more motivated to receive treatment ( 25 ). A study by Chinese scholars reported ( 26 )that there was a significant correlation between psychological resilience and illness stigma. Patients with a high level of psychological resilience can help maintain a stable psychological and physiological state in unfavorable environments, promote more active participation in social activities, buffer the psychological sense of shame that occurs in patients as a result of the disease, and be more accepting of changes in somatic functioning as a result of the disease, thus reducing the emergence of other negative emotions.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, when dealing with the obstacles and challenges of their condition, it can assist people with chronic diseases in being more motivated to receive treatment ( 25 ). A study by Chinese scholars reported ( 26 )that there was a significant correlation between psychological resilience and illness stigma. Patients with a high level of psychological resilience can help maintain a stable psychological and physiological state in unfavorable environments, promote more active participation in social activities, buffer the psychological sense of shame that occurs in patients as a result of the disease, and be more accepting of changes in somatic functioning as a result of the disease, thus reducing the emergence of other negative emotions.…”
Section: Introductionmentioning
confidence: 99%